Volume 7B: Structures and Dynamics 2013
DOI: 10.1115/gt2013-95214
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Pad Clearance and Preload Manufacturing Tolerances on Tilting Pad Bearings Rotordynamic Coefficients

Abstract: Tilting pad bearings (TPB) are commonly used in high-speed and high-power turbomachines, due to its contributions in avoiding rotor instabilities. Studies related to the estimation of dynamic coefficients have been carried out considering a uniform value of the geometric parameters (clearance, pre-load) for all bearing pads. These assumptions give a reasonable agreement on the direct coefficients prediction while, recently, some discrepancies have been found on the cross-coupled coefficients. In this work, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The current trend in the industrial field is to increase the dynamic performances of rotating machinery by installing high-preloaded TPJBs to obtain high dynamic coefficients. 20,21 Therefore, manufacturing errors in the loaded pads are notably critical to the dynamic behaviour of the machine. The dynamic stiffness and damping coefficients of all bearings as a function of the rotational speed are shown in Figures 13 and 15 for all three cases.…”
Section: Dynamic Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current trend in the industrial field is to increase the dynamic performances of rotating machinery by installing high-preloaded TPJBs to obtain high dynamic coefficients. 20,21 Therefore, manufacturing errors in the loaded pads are notably critical to the dynamic behaviour of the machine. The dynamic stiffness and damping coefficients of all bearings as a function of the rotational speed are shown in Figures 13 and 15 for all three cases.…”
Section: Dynamic Coefficientsmentioning
confidence: 99%
“…The effect of pad clearance and preload variation on the dynamic coefficients of a five-pad TPJB was also investigated using a numerical model in literature. 20,21 These papers concluded that the manufacturing tolerances might introduce major effects on the dynamic coefficients of a TPJB. However, these two researches only focused on the dynamic coefficients of the bearings installed in a LOP configuration as a function of excitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, an increase in the sleeve bearing wear severity can lead to decrease in bearing stiffness [45], according to Figures 10 and 11, the increase in the wear severity in TPJBs with load between pads (LBP) configuration results in an increase in direct dynamic coefficients due to the enhancement of the wear-induced asymmetry and preload of the TPJBs. The increase in TPJBs dynamic coefficients with LBP configuration due to the bearing preload and bearing asymmetry enhancement was also discussed in [5,46,47]. 253.3% In the proposed model, flexible rotor vibration amplitudes are obtained at the disc and the journal locations using the calculated dynamic coefficients as shown in Figure 12.…”
Section: Resultsmentioning
confidence: 95%
“…However, an increase in the sleeve bearing wear severity can lead to decrease in bearing stiffness [59], according to Figures 10 and 11, the increase in the wear severity in TPJBs with load between pads (LBP) configuration results in an increase in direct dynamic coefficients due to the enhancement of the wearinduced asymmetry and preload of the TPJBs. The increase in TPJBs dynamic coefficients with LBP configuration due to the bearing preload and bearing asymmetry enhancement was also discussed in [5,60,61] In the proposed model, flexible rotor vibration amplitudes are obtained at the disc and the journal locations using the calculated dynamic coefficients as shown in Figure 12. This figure shows that the high damping of the TPJB results in the creation of a flat peak.…”
Section: Resultsmentioning
confidence: 97%
“…However, an increase in the sleeve bearing wear severity can lead to decrease in bearing stiffness [59], according to Figures 10 and 11, the increase in the wear severity in TPJBs with load between pads (LBP) configuration results in an increase in direct dynamic coefficients due to the enhancement of the wear-induced asymmetry and preload of the TPJBs. The increase in TPJBs dynamic coefficients with LBP configuration due to the bearing preload and bearing asymmetry enhancement was also discussed in [5,60,61].…”
Section: Resultsmentioning
confidence: 99%